Biomass-based multifunctional ion-electron type conductive hydrogel and preparation method thereof, and strain sensor

By combining gelatin with polyacrylamide and MXene nanosheets and introducing metal ions, biomass-based ion-electronic conductive hydrogel was prepared, and the problems of low mechanical properties and poor conductivity of gelatin conductive hydrogel were solved, achieving high The effect of sensitivity and wide sensing range is suitable for physiological signal detection and human-computer interaction.

CN119161599APending Publication Date: 2024-12-20SHAANXI UNIV OF SCI & TECH

Patent Information

Application Number
CN202411532504.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

In the prior art, gelatin as a conductive hydrogel base material has problems such as low mechanical properties, poor electrical conductivity, narrow sensing range and low sensitivity.

Method used

The biomass-based ion-electron type conductive hydrogel is prepared by combining gelatin with polyacrylamide and MXene nanosheets through thermal polymerization and crosslinking. The synergistic effect of MXene's conductive pathway and metal ions is used to improve the conductivity of the hydrogel and Mechanical properties and enhance cross-linking density through salting out of inorganic salt ions.

Benefits of technology

It significantly improves the conductivity, sensitivity and sensing range of the hydrogel, enhances mechanical properties, and has the biocompatibility and environmental protection of the material, suitable for detecting physiological signals and human-computer interaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses biomass-based multifunctional ion-electron type conductive hydrogel, a preparation method thereof and a strain sensor, and the preparation method comprises the following steps: uniformly mixing a gelatin solution and a polyacrylamide solution to obtain a gelatin-polyacrylamide solution; adding the MXene nanosheet dispersion liquid into a mixed salt solution of two different metal ions to obtain an MXene nanosheet-metal ion composite solution; the metal ions are monovalent or divalent; and uniformly mixing the MXene nanosheet-metal ion composite solution with a gelatin-polyacrylamide solution, and carrying out thermal polymerization crosslinking, so as to obtain the biomass-based ion-electron type conductive hydrogel. According to the invention, polyacrylamide is introduced into a gelatin system, MXene and a metal ion composite conductive material are utilized to provide a conductive path for a hydrogel network, the electron transmission rate is enhanced, the mechanical strength of the hydrogel network is improved, and a foundation is laid for enhancement of the conductivity, sensitivity and tensile strength of the sensor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of development of flexible sensing materials, and relates to a biomass-based multifunctional ion-electronic conductive hydrogel and a preparation method thereof, and a strain sensor. Background Art

[0002] As people's awareness of environmental protection and health increases, some environmentally unfriendly synthetic polymer materials are gradually replaced by environmentally friendly biomass materials. Biomass materials are derived from living organisms such as animals and plants. Due to their unique spatial conformation and chemical composition, as well as their many advantages such as easy functionalization, skin-friendly and breathable, biocompatible, biodegradable, environmentally friendly and low-cost, they show great potential in the field of conductive hydrogel-based flexible sensing materials. Therefore, the development and exploration of multifunctional biomass-based conductive hydrogels is the main research direction of flexible sensing materials in the future.

[0003] Gelatin has good stability, degradability, unique multi-layered structure and rich functional groups, so it helps to construct sensitive sensing units and sensing networks, and provides good comfort, safety and long life for wearable devices. Liu et al. (Liu C, et al. Advanced Composites and Hybrid Materials, 2023, 6(3): 112.) incorporated poly (3, 4-ethylenedioxythiophene): poly (styrene sulfonic acid) into the gelatin network and prepared a multimodal gelatin-based hydrogel sensor using a thermal enhancement strategy, which showed good stability in sensing and monitoring strain and humidity. Qin et al. (Qin X, et al. Carbohydrate Polymers, 2024, 335: 121920.) synthesized a double network hydrogel using gelatin and sodium oxidized carboxymethyl cellulose as raw materials, and used the Hofmeister effect between gelatin and salt to enhance the mechanical properties and conductive properties of the hydrogel, and applied it to the monitoring of human joint movement. Cheng et al. (Cheng J, et al. ACS Applied Materials&Interfaces, 2022, 14(23): 26338-26349.) incorporated polyaniline, reduced graphene oxide and silver nanowires into a gelatin hydrogel matrix to prepare wearable flexible sensors. The obtained sensors maintained well-distributed porosity, air permeability and mechanical flexibility, and were successfully used to detect physiological signals and human-computer interaction. However, gelatin as a base material has defects such as low mechanical properties, poor conductivity, narrow sensing range and low sensitivity. Summary of the invention

[0004] In view of the problems existing in the prior art, the present invention provides a biomass-based multifunctional ion-electronic conductive hydrogel and a preparation method thereof, and a strain sensor, thereby solving the technical problems in the prior art of low mechanical properties, poor conductivity, narrow sensing range and low sensitivity when gelatin is used as a conductive hydrogel base material.

[0005] The present invention is achieved through the following technical solutions: A method for preparing a biomass-based ion-electronic conductive hydrogel comprises the following steps: S1: uniformly mixing the gelatin solution and the polyacrylamide solution to obtain a gelatin-polyacrylamide solution; adding the MXene nanosheet dispersion to a mixed salt solution of two different metal ions to obtain a MXene nanosheet-metal ion composite solution; the metal ions are monovalent or divalent; S2: The MXene nanosheet-metal ion composite solution and the gelatin-polyacrylamide solution are mixed evenly, and after thermal polymerization and cross-linking, the biomass-based ion-electronic conductive hydrogel is obtained.

[0006] Preferably, in step S1, polyacrylamide is prepared by mixing acrylamide, N-N'methylenebisacrylamide, ammonium persulfate and water; wherein the mass ratio of acrylamide to N-N'methylenebisacrylamide is (0.05-0.5):(0.005-0.01); The volume ratio of the gelatin solution to the polyacrylamide solution is (0.4-1.2):1, and the concentration of the gelatin solution is 0.2-0.6 g / mL.

[0007] Preferably, in step S1, the preparation process of the gelatin-polyacrylamide solution is: adding the gelatin solution into the polyacrylamide solution, stirring evenly, and standing to degas, so as to obtain the gelatin-polyacrylamide solution.

[0008] Preferably, in step S1, the concentration of the MXene nanosheet dispersion is 5.0-20.0 mg / mL, the concentrations of the two different metal ion salt solutions are both 0.5-3.5 mol / L, and the volume ratio of the MXene nanosheet dispersion to the mixed salt solution is (1-5):(1-5).

[0009] Preferably, the metal ion is Na + , K + , Li + 、Ag + , Ca 2+ 、Zn 2+ Mg 2+ , Cu 2+ and Fe 2+ Any two of .

[0010] Preferably, in step S1, in the mixed salt solution of the two different metal ions, the molar amounts of the two metal ions are the same.

[0011] Preferably, in step S2, the volume ratio of the MXene nanosheet-metal ion composite solution to the gelatin-polyacrylamide solution is (2-8.5):(5-30).

[0012] Preferably, in step S2, during the thermal polymerization cross-linking process, the temperature is 60-115° C. and the time is 1.5-3.5 h.

[0013] A biomass-based ion-electronic conductive hydrogel is prepared by the above method; the conductive hydrogel has a conductivity of 4.3-4.5 S / m, a tensile strength of 100-105 kPa, and an elongation at break of 1000%-1100%.

[0014] A strain sensor comprises the above-mentioned biomass-based ion-electronic conductive hydrogel.

[0015] Compared with the prior art, the present invention has the following beneficial technical effects: The present invention discloses a method for preparing a biomass-based ion-electronic conductive hydrogel. The method firstly uses gelatin with good biocompatibility and flexibility as the main network to form an interaction with polyacrylamide. Polyacrylamide can give the gel good stretchability, thereby increasing the stability, applicability and comfort of the hydrogel. Secondly, MXene, as a two-dimensional layered nanomaterial, has a large number of surface active sites and can strongly interact with surrounding molecules or lattices. Moreover, since the metal substrate it contains has high strength and hardness, it has good mechanical properties and can provide good mechanical support for the hydrogel. Inorganic salt ions can interact with polymer chains through salting out. Form strong interactions (such as: intermolecular interactions, hydrogen bonding), thereby increasing the crosslinking density of the hydrogel network and enhancing its mechanical properties; again, MXene contains a large number of conductive pathways, allowing electrons to be freely transmitted between layers, and the metal substrate and two-dimensional layered structure it contains are conducive to improving electron mobility, so it can effectively enhance the conductivity of the gel; inorganic salt ions can introduce additional free electrons or holes into the gel, thereby increasing the carrier concentration of the material, and the conductive pathways formed by them can effectively reduce the scattering loss of electrons and enhance electron transmission, thereby improving the conductivity of the material, so that it can be used to detect physiological signals and human-computer interaction, and the sensing range is wide and the sensitivity is high. At the same time, the present invention uses two different metal ions to effectively improve the conductivity, sensitivity and sensing range of the hydrogel. Furthermore, there are a large number of pore structures and binding sites in the network structure of gelatin and polyacrylamide, and these pores and binding sites can accommodate, adsorb and preserve water molecules, so that the hydrogel has good moisturizing properties, and the raw materials used in the preparation process of the hydrogel are non-toxic and harmless, so they will not pollute the environment, and are more green and environmentally friendly.

[0016] Furthermore, another inventive point of the present invention is that in step S1, polyacrylamide is prepared by mixing acrylamide, N-N'methylenebisacrylamide, ammonium persulfate and water; wherein the mass ratio of acrylamide to N-N'methylenebisacrylamide is (0.05~0.5):(0.005~0.01), the volume ratio of the gelatin solution to the polyacrylamide solution is (0.4~1.2):1, the concentration of the gelatin solution is 0.2~0.6g / mL, and polyacrylamide is prepared by mixing acrylamide (main monomer), N-N'methylenebisacrylamide (cross-linking agent), ammonium persulfate (initiator) and water. The polymerization reaction forms a certain cross-linking structure between the molecular chains of polyacrylamide through the addition of the cross-linking agent N-N'methylenebisacrylamide, thereby giving it good mechanical strength and stretchability. The mass ratio of acrylamide to N-N'methylenebisacrylamide is set to (0.05~0.5):(0.005~0.01). Too little cross-linking agent cannot form enough cross-linking points, resulting in insufficient mechanical properties of polyacrylamide, while too much cross-linking agent makes the polymer network too tight, affecting the flexibility and conductivity of the hydrogel. Therefore, this ratio range can maintain the flexibility and conductivity of the hydrogel while ensuring mechanical strength. The volume ratio of gelatin solution to polyacrylamide solution is set to (0.4~1.2):1. As the main network structure of the hydrogel, the content of gelatin has an important influence on the biocompatibility, flexibility and mechanical properties of the hydrogel. The right amount of gelatin can provide good biocompatibility and flexibility, and form a stable interaction with polyacrylamide. Too little gelatin cannot form enough network structure, resulting in a decrease in the mechanical properties of the hydrogel, while too much gelatin may make the hydrogel too soft, affecting its performance. Therefore, this ratio range can ensure the flexibility of the hydrogel while giving it sufficient mechanical strength and stability. The concentration of the gelatin solution is 0.2~0.6g / mL, which can ensure that the gelatin is fully dissolved in the aqueous solution to form a uniform solution, which is beneficial to the subsequent mixing and cross-linking reaction with polyacrylamide. Too low a concentration will cause the gelatin solution to be too thin and unable to form a stable network structure; while too high a concentration will make the solution too viscous, affecting the mixing uniformity and cross-linking effect. Therefore, this concentration range can improve the efficiency of mixing and cross-linking while ensuring the stability of the solution.

[0017] Furthermore, another inventive point of the present invention is that in step S1, the preparation process of the gelatin-polyacrylamide solution is: adding the gelatin solution to the polyacrylamide solution, stirring evenly, and standing to degas, so as to obtain the gelatin-polyacrylamide solution. By stirring, it can be ensured that the gelatin solution and the polyacrylamide solution are fully mixed to form a uniform mixture. The step of standing to degas is the key to removing the bubbles generated during the mixing process. The presence of bubbles will not only affect the appearance of the hydrogel, but more importantly, they may act as stress concentration points to reduce the mechanical properties of the hydrogel. By standing to degas, these bubbles can be minimized or eliminated, thereby improving the overall quality of the hydrogel; the interaction between gelatin and polyacrylamide is strengthened during the stirring process, and this interaction helps to form a more stable network structure. The stable network structure is the basis for preparing high-performance hydrogels. It can resist the interference of external factors (such as temperature, humidity, etc.) and maintain the durability of the hydrogel performance.

[0018] Further, another inventive point of the present invention is that in step S1, the concentration of the MXene nanosheet dispersion is 5.0~20.0mg / mL, the concentration of the two different metal ion salt solutions is 0.5~3.5mol / L, the volume ratio of the MXene nanosheet dispersion to the mixed salt solution is (1~5):(1~5), and the concentration of the MXene nanosheet dispersion is set to 5.0~20.0mg / mL. This range ensures the uniform dispersion of the MXene nanosheets in the dispersion, and it is neither too sparse to cause insufficient binding with metal ions, nor too dense to cause agglomeration, thereby ensuring the effective utilization of the MXene nanosheets. The concentrations of the two different metal ion salt solutions are both set to 0.5~3.5mol / L. This concentration range allows the metal ions to fully dissolve in the solution and interact effectively with the MXene nanosheets. At the same time, the use of two different metal ions may bring about a synergistic effect, further improving the performance of the hydrogel. The volume ratio of MXene nanosheet dispersion to mixed salt solution is (1~5):(1~5), which helps to form a uniform composite structure between MXene nanosheets and metal ions. The active sites on the surface of MXene nanosheets can adsorb and bind metal ions, and the appropriate concentration and volume ratio make this combination more sufficient and effective. This composite structure not only enhances the mechanical properties of the hydrogel, but also improves its electrical conductivity. The introduction of metal ions provides an additional conductive pathway for the hydrogel, and the MXene nanosheets themselves have good electrical conductivity. By optimizing the concentration and volume ratio of MXene nanosheet dispersion to metal ions, their electrical conductivity can be maximized, so that the final hydrogel has excellent electrical conductivity.

[0019] Furthermore, another inventive point of the present invention is that in step S1, in the mixed salt solution of the two different metal ions, the molar amounts of the two metal ions are the same. First, when the molar amounts of the two metal ions are the same, their adsorption and binding effects on the surface of the MXene nanosheets will be relatively balanced. This balance helps to form a more stable and uniform composite structure, avoiding the problem of local aggregation or uneven interaction caused by differences in metal ion concentrations. The type and proportion of metal ions have a significant effect on the performance of the hydrogel. When the molar amounts of the two metal ions are the same, they may work in a more synergistic manner to optimize the conductivity, mechanical properties, stability, etc. of the hydrogel. This optimization effect may enable the hydrogel to exhibit more excellent performance in specific application fields.

[0020] Further, another inventive point of the present invention is that in step S2, the volume ratio of the MXene nanosheet-metal ion composite solution to the gelatin-polyacrylamide solution is (2~8.5): (5~30). First, by adjusting the volume ratio of the two solutions, the dispersion degree and content of the MXene nanosheet-metal ion complex in the gelatin-polyacrylamide matrix can be accurately controlled, which directly affects the physical, chemical and mechanical properties of the final composite material. The appropriate volume ratio helps to ensure that the MXene nanosheet-metal ion complex is evenly distributed in the gelatin-polyacrylamide matrix to avoid local aggregation or the formation of voids. This uniformity is crucial to improving the overall performance and stability of the composite material. The combination of MXene nanosheets and metal ions and their interaction with the gelatin-polyacrylamide matrix together constitute a stable structure of the composite material. By adjusting the volume ratio, the interaction between the components can be optimized, thereby improving the thermal stability, chemical stability and mechanical stability of the composite material.

[0021] Further, another inventive point of the present invention is that in step S2, during the thermal polymerization cross-linking process, the temperature is 60-115°C and the time is 1.5-3.5h. First, within this temperature range, gelatin and polyacrylamide molecular chains can undergo effective cross-linking reactions. Higher temperatures can accelerate the movement of molecular chains, making them more likely to contact each other and undergo chemical reactions, thereby ensuring that the cross-linking reaction is fully carried out. At the same time, a sufficiently long time (1.5-3.5h) also ensures that the cross-linking reaction is thoroughly completed, avoiding incomplete cross-linking or performance degradation caused by insufficient reaction time. In addition, by adjusting the temperature and time, the density of the cross-linking reaction can be accurately controlled. Higher temperatures and longer times usually lead to higher cross-linking densities, thereby improving the mechanical strength and stability of the composite material. However, excessive cross-linking densities may also cause the material to become brittle, so it is necessary to select a suitable temperature and time combination while ensuring performance. At the same time, long-term cross-linking reactions at high temperatures can induce some undesirable side reactions, such as degradation of molecular chains or excessive cross-linking, etc. By accurately controlling the temperature and time, the occurrence of these side reactions can be reduced, thereby maintaining the stability and performance of the composite material. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0023] Figure 1 The gelatin-polyacrylamide-MXene / K prepared in Example 1 of the present invention + / Ca 2+ Conductivity plot of the hydrogel; Figure 2 The gelatin-polyacrylamide-MXene / K prepared in Example 1 of the present invention + / Ca 2+ Tensile strength and elongation at break of hydrogels; Figure 3 The gelatin-polyacrylamide-MXene / K prepared in Example 1 of the present invention + / Ca 2+ Relative resistance change of the hydrogel. DETAILED DESCRIPTION

[0024] In order to enable those skilled in the art to understand the characteristics and effects of the present invention, the following is a general description and definition of the terms and expressions mentioned in the specification and claims. Unless otherwise specified, all technical and scientific terms used in the text are the common meanings understood by those skilled in the art for the present invention. In the event of a conflict, the definition in this specification shall prevail.

[0025] The theories or mechanisms described and disclosed herein, whether correct or incorrect, should not limit the scope of the present invention in any way, that is, the present invention can be implemented without being limited by any specific theory or mechanism.

[0026] In this article, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are for simplicity and convenience only. Accordingly, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values ​​within the range (including integers and fractions).

[0027] In this document, unless otherwise specified, “includes,” “including,” “contains,” “has,” or similar terms cover the meanings of “consisting of” and “mainly consisting of,” for example, “A includes a” covers the meanings of “A includes a and other” and “A only includes a.”

[0028] In this document, in order to make the description concise, not all possible combinations of various technical features in various embodiments or examples are described. Therefore, as long as there is no contradiction in the combination of these technical features, the various technical features in various embodiments or examples can be combined arbitrarily, and all possible combinations should be considered to be within the scope of this specification.

[0029] The present invention provides a method for preparing a biomass-based ion-electronic conductive hydrogel, the steps of which are as follows: S1: uniformly mixing the gelatin solution and the polyacrylamide solution to obtain a gelatin-polyacrylamide solution; adding the MXene nanosheet dispersion to a mixed salt solution of two different metal ions to obtain a MXene nanosheet-metal ion composite solution; the metal ions are monovalent or divalent; Wherein, polyacrylamide is prepared by mixing acrylamide, N-N'methylenebisacrylamide, ammonium persulfate and water; wherein the mass ratio of acrylamide to deionized water is (0.05-0.5):1, the mass ratio of acrylamide to N-N'methylenebisacrylamide is (0.05-0.5):(0.005-0.01), and the mass ratio of acrylamide to ammonium persulfate is (0.05-0.5):(0.005-0.02); The volume ratio of the gelatin solution to the polyacrylamide solution is (0.4-1.2):1, and the concentration of the gelatin solution is 0.2-0.6 g / mL, that is, in the gelatin solution, the ratio of gelatin to deionized water is (0.2-0.6):1 mL.

[0030] The preparation process of the gelatin-polyacrylamide solution is as follows: adding the gelatin solution into the polyacrylamide solution, stirring evenly, and standing to degas, so as to obtain the gelatin-polyacrylamide solution.

[0031] The concentration of the MXene nanosheet dispersion is 5.0-20.0 mg / mL, the concentrations of the two different metal ion salt solutions are both 0.5-3.5 mol / L, and the volume ratio of the MXene nanosheet dispersion to the mixed salt solution is (1-5):(1-5). The volume ratio of the two different metal ion salt solutions is 1:1.

[0032] The metal ion is Na + , K + , Li + 、Ag + , Ca 2+ 、Zn 2+ Mg 2+ , Cu 2+ and Fe 2+ In the mixed salt solution of the two different metal ions, the molar amounts of the two metal ions are the same.

[0033] S2: The MXene nanosheet-metal ion composite solution and the gelatin-polyacrylamide solution are mixed evenly, and after thermal polymerization and cross-linking, the biomass-based ion-electronic conductive hydrogel is obtained.

[0034] The volume ratio of the MXene nanosheet-metal ion composite solution to the gelatin-polyacrylamide solution is (2-8.5):(5-30).

[0035] During the thermal polymerization cross-linking process, the temperature is 60-115° C. and the time is 1.5-3.5 hours.

[0036] In this step, specifically, the MXene nanosheet-metal ion composite solution is added to the gelatin-polyacrylamide solution, and after mechanical stirring until it is completely uniform, it is allowed to stand for degassing and then transferred to a mold, and the biomass-based ion-electronic conductive hydrogel is obtained through thermal polymerization and cross-linking.

[0037] In addition, the present invention also discloses a biomass-based ion-electron conductive hydrogel prepared by the above method, wherein the conductivity of the conductive hydrogel is 4.3-4.5 S / m, which is 5764.36%-6014.21% higher than that of the hydrogel sensor without the introduction of ion-electron conductive material. The tensile strength of the biomass-based ion-electron conductive hydrogel in the present invention is 100-105 kPa, and the elongation at break is 1000%-1100%.

[0038] The present invention adopts two different metal ions, which can effectively improve the conductivity, sensitivity and sensing range of hydrogel. First, for ion conductive hydrogel, its own current conduction is realized by providing ion migration through inorganic salts or ionic liquids. This process requires ion transport channels and water environment. Since its resistance change in the stretching process is closely related to the deformation degree, it has a wider sensing range, but the sensitivity is low in a small strain range, and the two ions can produce more abundant free ions. The ionic current produced by the directional migration of these free ions under the action of the electric field can make the hydrogel have a higher conductivity, that is, the ion or carrier concentration in the hydrogel increases, so it helps to improve the response speed, sensitivity and sensing range of the sensor. In addition, the two ions can form a more stable network structure through the synergistic effect between ions, and the potential difference formed by the difference in ion mobility can also be used to improve the conductivity of the hydrogel, so it helps to improve the various properties of the hydrogel. In addition, for the selection of ions, first, the interaction between ions, polymer molecular chains and hydration will change because of the difference in ion species. Secondly, the polyacrylamide-gelatin-MXene hydrogel precursor itself is negatively charged, so the introduction of monovalent or divalent cations is selected to improve the structure and performance of the hydrogel.

[0039] The invention also discloses a strain sensor comprising the biomass-based ion-electron conductive hydrogel.

[0040] The present invention discloses a biomass-based multifunctional ion-electronic conductive hydrogel and a preparation method thereof. Gelatin is used as a biomass base material to form a double network structure with polyacrylamide, and then MXene / M + / N 2+ Ion-electron complex solution (here, M + Represents a monovalent metal ion, N 2+ represents divalent metal ions, and of course can also be different monovalent metal ions or different divalent metal ions), and the gelatin-based conductive hydrogel is prepared by a one-pot method.

[0041] Performance analysis of the conductive hydrogel: Analysis of the conductive properties: First, MXene contains a large number of conductive pathways, which enable electrons to be transmitted freely between layers, and the metal substrate and two-dimensional layered structure it contains are conducive to improving electron mobility, thereby effectively enhancing the conductive properties of the gel; secondly, inorganic salt ions can introduce additional free electrons or holes into the gel, thereby increasing the carrier concentration of the material, and the conductive pathways formed by them can effectively reduce electron scattering losses and enhance electron transmission, thereby improving the conductive properties of the material.

[0042] Analysis of its mechanical properties: First, gelatin with good biocompatibility and softness is used as the main network to form an interaction with polyacrylamide. Polyacrylamide can give the gel good stretchability and increase the accuracy, applicability and comfort of the hydrogel. Secondly, MXene, as a two-dimensional layered nanomaterial, has a large number of surface active sites and can interact strongly with the surrounding molecules or lattices. Moreover, because the metal substrate it contains has high strength and hardness, it has good mechanical properties and can provide good mechanical support for the hydrogel. In addition, inorganic salt ions can form strong interactions with polymer chains through salting out (such as intermolecular interactions and hydrogen bonding), thereby increasing the cross-linking density of the hydrogel network and enhancing its mechanical properties.

[0043] Analysis of environmental stability: First, there are a large number of pore structures and binding sites in the network structure of gelatin and polyacrylamide. These pores and binding sites can accommodate, adsorb and preserve water molecules, giving the hydrogel good moisturizing properties; secondly, the raw materials used in the preparation process of the hydrogel are non-toxic and harmless, so they will not pollute the environment.

[0044] The present invention discloses a method for preparing a gelatin-based hydrogel sensing material. By using gelatin as a matrix material, the material has the advantages of low price, skin-friendly, breathable, non-toxic and environmentally friendly. The unique spiral structure of gelatin has excellent flexibility, softness, and water permeability. At the same time, the interpenetrating network structure formed between gelatin and polyacrylamide can not only improve the strong stretchability and flexibility of the hydrogel, but also provide more binding sites for the conductive material. Then, MXene / M m + / N n+ The mixed solution was introduced into the polyacrylamide-gelatin network structure (here, m+ represents the valence of metal M, n+represents the valence of metal N), while enhancing the mechanical properties of the hydrogel, the conductivity and sensing properties are effectively improved. Therefore, the preparation method of the present invention can not only give full play to the advantages of gelatin itself, such as good softness and air permeability, greenness and pollution-free, so that the final gelatin-based hydrogel sensing material has good flexibility and air permeability, but also avoid the generation of a large number of environmental hazards. Among them, the gelatin-polyacrylamide interpenetrating network structure is conducive to the introduction of conductive materials, etc., so many manufacturing processes can be avoided. In addition, the present invention combines gelatin with polyacrylamide, MXene / M by simple mechanical stirring. m+ / N n+ The polymerization process is simple and has the advantages of low energy consumption and low cost. It can be widely used in human-computer interaction, medical health, rehabilitation therapy and other fields, and is beneficial to large-scale industrial production.

[0045] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0046] The following examples use conventional instruments and equipment in the art. The experimental methods in the following examples where specific conditions are not specified are usually carried out under conventional conditions or under conditions recommended by the manufacturer. The various raw materials used in the following examples are conventional commercial products unless otherwise specified, and their specifications are conventional specifications in the art. In the specification of the present invention and the following examples, unless otherwise specified, "%" means weight percentage, "part" means weight part, and ratio means weight ratio.

[0047] Example 1 (1) acrylamide, deionized water, N-N'methylenebisacrylamide and ammonium persulfate in a mass ratio of 0.4:1:0.004:0.008 were mixed and stirred to obtain a polyacrylamide solution; a gelatin solution with a mass fraction of 60wt% and a polyacrylamide mixed solution with a mass fraction of 40wt% were mixed in a volume ratio of 0.5:1, mechanically stirred until completely uniform, and then allowed to stand for degassing to obtain a gelatin-polyacrylamide transparent solution; (2) 2 mL of K with an ion concentration of 3 mol / L was added to each + and Ca 2+ After mixing evenly in a volume ratio of 1:1, 3 mL of MXene nanosheet dispersion with a mass concentration of 13.0 mg / mL was introduced and mechanically stirred in an ice water bath until completely uniform to obtain MXene / K + / Ca 2+ Ion-electron complex solution; (3) MXene / K + / Ca 2+ The ion-electron mixed solution was added to the gelatin-polyacrylamide solution at a volume ratio of 7:12, stirred until completely uniform, and then allowed to stand for degassing before being transferred to the mold. The mixture was reacted at 80 °C for 2 h, and the microstructured gelatin-polyacrylamide-MXene / K was obtained by thermal polymerization and crosslinking. + / Ca 2+ Ionic / electronic conductive hydrogels.

[0048] Example 2 (1) acrylamide, deionized water, N-N'methylenebisacrylamide and ammonium persulfate in a mass ratio of 0.5:1:0.005:0.01 were mixed and stirred to obtain a polyacrylamide solution; a gelatin solution with a mass fraction of 50 wt% and a polyacrylamide mixed solution with a mass fraction of 50 wt% were mixed in a volume ratio of 0.85:1, mechanically stirred until completely uniform, and then allowed to stand for degassing to obtain a gelatin-polyacrylamide transparent solution; (2) 1.5 mL of Na2O3 with an ion concentration of 3.5 mol / L was added to each + and Zn 2+ After mixing evenly in a volume ratio of 1:1, 4 mL of MXene nanosheet dispersion with a mass concentration of 10.0 mg / mL was introduced and mechanically stirred in an ice water bath until completely uniform to obtain MXene / Na + / Zn 2+ Ion-electron complex solution; (3) MXene / Na + / Zn 2+ The ion-electron mixed solution was added to the gelatin-polyacrylamide solution at a volume ratio of 3:5, stirred until completely uniform, and then allowed to stand for degassing before being transferred to the mold. The mixture was reacted at 65 °C for 3 h, and the microstructured gelatin-polyacrylamide-MXene / Na was obtained by thermal polymerization and cross-linking. + / Zn 2+ Ionic / electronic conductive hydrogels.

[0049] Example 3 (1) acrylamide, deionized water, N-N'methylenebisacrylamide and ammonium persulfate in a mass ratio of 0.6:1:0.006:0.012 were mixed and stirred to obtain a polyacrylamide solution; a gelatin solution with a mass fraction of 35wt% and a polyacrylamide mixed solution with a mass fraction of 60wt% were mixed in a volume ratio of 1.2:1, mechanically stirred until completely uniform, and then allowed to stand for degassing to obtain a gelatin-polyacrylamide transparent solution; (2) 2.5 mL of Li + and Mg 2+After mixing evenly in a volume ratio of 1:1, 2 mL of MXene nanosheet dispersion with a mass concentration of 15.0 mg / mL was introduced and mechanically stirred in an ice water bath until completely uniform to obtain MXene / Li + / Mg 2+ Ion-electron complex solution; (3) MXene / Li + / Mg 2+ The ion-electron mixed solution was added to the gelatin-polyacrylamide solution at a volume ratio of 7:17, stirred until completely uniform, and then placed to degas before being transferred to the mold. The mixture was reacted at 100°C for 1.5h, and the microstructured gelatin-polyacrylamide-MXene / Li was obtained by thermal polymerization and cross-linking. + / Mg 2+ Ionic / electronic conductive hydrogels.

[0050] Example 4 A method for preparing a biomass-based ion-electronic conductive hydrogel, comprising the following steps: S1: acrylamide, N-N'methylenebisacrylamide, ammonium persulfate and water in a mass ratio of 0.05:0.005:0.005:1 are uniformly mixed to prepare a polyacrylamide solution. The gelatin solution with a concentration of 0.2 g / mL and the polyacrylamide solution were mixed evenly at a volume ratio of 0.4:1, and allowed to stand for degassing to obtain the gelatin-polyacrylamide solution; A MXene nanosheet dispersion with a concentration of 5.0 mg / mL was added to a mixed salt solution of two different metal ions at a volume ratio of 1:1 to obtain a MXene nanosheet-metal ion composite solution; wherein, in the mixed salt solution of two different metal ions, the concentrations of the two different metal ion salt solutions were both 0.5 mol / L, and the metal ion was Li + With Ca 2+ .

[0051] S2: The MXene nanosheet-metal ion composite solution and the gelatin-polyacrylamide solution are mixed uniformly at a volume ratio of 2:5, treated at 60°C for 3.5 hours, and cross-linked by thermal polymerization to obtain the biomass-based ion-electronic conductive hydrogel. The conductive hydrogel obtained in this embodiment has a conductivity of 4.3S / m, a tensile strength of 102kPa, and an elongation at break of 1005.3%.

[0052] Example 5 A method for preparing a biomass-based ion-electronic conductive hydrogel, comprising the following steps: S1: acrylamide, N-N'methylenebisacrylamide, ammonium persulfate and water in a mass ratio of 0.5:0.01:0.02:1 are uniformly mixed to prepare a polyacrylamide solution. The gelatin solution with a concentration of 0.6 g / mL and the polyacrylamide solution were mixed evenly at a volume ratio of 1.2:1, and allowed to stand for degassing to obtain the gelatin-polyacrylamide solution; A MXene nanosheet dispersion with a concentration of 20.0 mg / mL was added to a mixed salt solution of two different metal ions at a volume ratio of 5:2 to obtain a MXene nanosheet-metal ion composite solution; wherein, in the mixed salt solution of two different metal ions, the concentrations of the two different metal ion salt solutions were both 3.5 mol / L, and the metal ion was Ag. + With Mg 2+ .

[0053] S2: The MXene nanosheet-metal ion composite solution and the gelatin-polyacrylamide solution are mixed uniformly at a volume ratio of 8.5:30, treated at 115°C for 1.5 hours, and cross-linked by thermal polymerization to obtain the biomass-based ion-electronic conductive hydrogel. The conductive hydrogel obtained in this embodiment has a conductivity of 4.5S / m, a tensile strength of 105.5kPa, and an elongation at break of 1102.3%.

[0054] Example 6 A method for preparing a biomass-based ion-electronic conductive hydrogel, comprising the following steps: S1: acrylamide, N-N'methylenebisacrylamide, ammonium persulfate and water in a mass ratio of 0.1:0.008:0.01:1 are uniformly mixed to prepare a polyacrylamide solution. The gelatin solution with a concentration of 0.4 g / mL and the polyacrylamide solution were mixed evenly at a volume ratio of 1:1, and allowed to stand for degassing to obtain the gelatin-polyacrylamide solution; A MXene nanosheet dispersion with a concentration of 10 mg / mL was added to a mixed salt solution of two different metal ions at a volume ratio of 2:3 to obtain a MXene nanosheet-metal ion composite solution; wherein, in the mixed salt solution of two different metal ions, the concentrations of the two different metal ion salt solutions were both 2 mol / L. The metal ion was Ca 2+ With Cu 2+ .

[0055] S2: The MXene nanosheet-metal ion composite solution and the gelatin-polyacrylamide solution are mixed uniformly at a volume ratio of 5:20, treated at 90°C for 2 hours, and cross-linked by thermal polymerization to obtain the biomass-based ion-electronic conductive hydrogel. The conductive hydrogel obtained in this embodiment has a conductivity of 4.36S / m, a tensile strength of 103.6kPa, and an elongation at break of 1050.7%.

[0056] Figure 1The gelatin-polyacrylamide-MXene / K prepared in Example 1 of the present invention + / Ca 2+ Comparison of the electrical conductivity of the hydrogel and the hydrogel prepared without adding metal ions. It can be seen from the figure that after the introduction of the ion mixed solution into the hydrogel system, the electrical conductivity of the hydrogel increased from 0.075 S / m to 4.41 S / m.

[0057] Figure 2 The gelatin-polyacrylamide-MXene / K prepared in Example 1 of the present invention + / Ca 2+ Comparison of the tensile strength and elongation at break of the hydrogel and the hydrogel without metal ions. It can be seen from the figure that gelatin-polyacrylamide-MXene / K + / Ca 2+ The mechanical strength of the hydrogel is 105.73 kPa, which is 32.74% higher than that of gelatin-polyacrylamide-MXene hydrogel (79.65 kPa). Its elongation at break is 1055.08%, which is 51.45% higher than that of the hydrogel without added metal ions (696.67%). Figure 3 The gelatin-polyacrylamide-MXene / K prepared in Example 1 of the present invention + / Ca 2+ The relative resistance change of the hydrogel is shown in the figure. In the strain range of 0~300%, gelatin-polyacrylamide-MXene / K + / Ca 2+ The sensitivity of the hydrogel is 1.59, and within the strain range of 300% to 700%, the sensitivity of the hydrogel is 3.85.

[0058] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

[0059] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing a biomass-based ion-electronic conductive hydrogel, characterized in that: The following steps are involved: S1: mixing the gelatin solution and the polyacrylamide solution evenly to obtain a gelatin-polyacrylamide solution; The MXene nanosheet dispersion is added into a mixed salt solution of two different metal ions to obtain a MXene nanosheet-metal ion composite solution; The metal ion is monovalent or divalent; S2: The MXene nanosheet-metal ion composite solution and the gelatin-polyacrylamide solution are mixed evenly, and after thermal polymerization and cross-linking, the biomass-based ion-electronic conductive hydrogel is obtained.

2. The method for preparing a biomass-based ion-electronic conductive hydrogel according to claim 1, characterized in that: In step S1, polyacrylamide is prepared by mixing acrylamide, N-N'methylenebisacrylamide, ammonium persulfate and water; wherein the mass ratio of acrylamide to N-N'methylenebisacrylamide is (0.05-0.5):(0.005-0.01); The volume ratio of the gelatin solution to the polyacrylamide solution is (0.4-1.2):1, and the concentration of the gelatin solution is 0.2-0.6 g / mL.

3. The method for preparing a biomass-based ion-electronic conductive hydrogel according to claim 1, characterized in that: In step S1, the preparation process of the gelatin-polyacrylamide solution is: adding the gelatin solution into the polyacrylamide solution, stirring evenly, and standing to degas, so as to obtain the gelatin-polyacrylamide solution.

4. The method for preparing a biomass-based ion-electronic conductive hydrogel according to claim 1, characterized in that: In step S1, the concentration of the MXene nanosheet dispersion is 5.0-20.0 mg / mL, the concentrations of the two different metal ion salt solutions are both 0.5-3.5 mol / L, and the volume ratio of the MXene nanosheet dispersion to the mixed salt solution is (1-5):(1-5).

5. The method for preparing a biomass-based ion-electronic conductive hydrogel according to claim 1, characterized in that: The metal ion is Na + , K + , Li + 、Ag + , Ca 2+ 、Zn 2+ Mg 2+ , Cu 2+ and Fe 2+ Any two of .

6. The method for preparing a biomass-based ion-electronic conductive hydrogel according to claim 1, characterized in that: In step S1, in the mixed salt solution of the two different metal ions, the molar amounts of the two metal ions are the same.

7. The method for preparing a biomass-based ion-electronic conductive hydrogel according to claim 1, characterized in that: In step S2, the volume ratio of the MXene nanosheet-metal ion composite solution to the gelatin-polyacrylamide solution is (2-8.5):(5-30).

8. The method for preparing a biomass-based ion-electronic conductive hydrogel according to claim 1, characterized in that: In step S2, during the thermal polymerization cross-linking process, the temperature is 60-115°C and the time is 1.5-3.5 hours.

9. A biomass-based ion-electron conductive hydrogel, characterized in that: Prepared by the method described in any one of claims 1 to 8; the conductivity of the conductive hydrogel is 4.3 to 4.5 S / m, the tensile strength is 100 to 105 kPa, and the elongation at break is 1000% to 1100%.

10. A strain sensor, characterized in that: The invention comprises a biomass-based ion-electronic conductive hydrogel as claimed in claim 9.

Citation Information

Patent Citations

  • Biodegradable triple network supramolecular elastomer hydrogel material, preparation method and application thereof

    CN109971000A

  • Ti<3>C<2>T<x> composite double-network hydrogel and preparation and application thereof

    CN110760075A

  • Amino modified MXene enhanced gelatin / chitosan composite hydrogel and preparation method thereof

    CN115010959A

  • Human motion monitoring system based on conductive elastomer

    CN118705988A

Cited By

  • Titanium carbide-metal ion conductive hydrogel with biological activity as well as preparation method and application of titanium carbide-metal ion conductive hydrogel

    CN121422302A